Migration routes and chronology of American Black Duck Anas rubripes - Coluccy, John M.; Anderson, Kurt A.; Yerkes, Tina; Bowman, Jacob L. (Wildfowl, 2020)
Satellite telemetry was used to identify migration routes and stopovers, estimate migration chronology, and describe variation in movements among American Black Duck Anas rubripes marked in Delaware, New Jersey, New York, Ohio and Virginia between 2007–2009. Thirty-one transmitters each provided data for at least one spring migration. The ducks departed their wintering areas during 18 March–7 June ( ± s.e. = 17 April ± 3.3 days), averaged 3.35 ± 0.3 stopovers (range = 1–5 stopovers) and spent 6.44 ± 0.8 days at stopover sites (range = 0.54–12.2 days), migrated 1,126.1 ± 89.5 km (range = 270–1,396 km), and arrived at inferred nesting areas during 16 April–28 June ( = 9 May ± 3.4 days). Black Duck on the South Atlantic Flyway migrated nearly twice as far (P < 0.01), made twice as many stopovers (P < 0.01) and arrived at their inferred nesting areas two weeks later than those on the North Atlantic and Mississippi Flyways (P = 0.04). Transmitters on 13 ducks provided at least partial data during autumn migrations. Black Duck departed inferred nesting or moulting areas during 5 October–1 December ( = 24 October ± 4.3 days), averaged 2.0 ± 0.3 stopovers (range = 1–4 stopovers), spent 12.6 ± 3.5 days at stopover sites (range = 0.25–41 days), migrated 993 ± 202.9 km (range = 277–1,485 km), and arrived at wintering areas during 18 November–18 December ( = 1 December ± 5.8 days). Our study confirmed known migration routes and stopovers and emphasises the need for habitat conservation and management along seasonal corridors, especially for Black Duck transitioning between their southern wintering and western breeding ranges. Furthermore, migration chronology and stopover duration of stay from our study should be incorporated into energetic carrying capacity models, to inform and direct habitat goals for Black Duck in north-eastern North America.